A Pengaruh Rasio Profitabilitas terhadap Price to Book Value (PBV) Pada Industri Tekstil dan Garmen di BEI Tahun 2020-2022 - Lestari, Lestari; Erdiana, Atty (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research examines the influence of Return on Assets (ROA) and Return On Equity (ROE) on the Price to Book Ratio with the research object of the textile and garment industry on the IDX in 2020-2022. The total population of this industry is 19 companies, and researchers used a saturated sampling technique so that a member of the population became the sample. The analysis technique used is multiple linear regression with the help of the SPSS statistical program. The research results show that return on assets (ROA) and return on equity (ROE) have a significant influence on price-to-book value (PBV). Meanwhile, partial Return on Assets (ROA) and Return On Equity (ROE) have a significant influence on Price to Book Value (PBV).